2015
DOI: 10.1109/tcsi.2015.2403032
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput LDPC-Decoder Architecture Using Efficient Comparison Techniques & Dynamic Multi-Frame Processing Schedule

Abstract: This paper presents architecture of block-level-parallel layered decoder for irregular LDPC code. It can be reconfigured to support various block lengths and code rates of IEEE 802.11n (WiFi) wireless-communication standard. We have proposed efficient comparison techniques for both column and row layered schedule and rejection-based high-speed circuits to compute the two minimum values from multiple inputs required for row layered processing of hardware-friendly min-sum decoding algorithm. The results show goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…The corresponding area efficiency of the proposed work is 76.81 Mbps/mm 2 , whereas the area efficiency obtained by Li et al [11], Park et al [18], Kumawat et al [19], and Lee et al [20] Table 2, it can be concluded that the proposed work is the most area-efficient among the reported LDPC decoders. Although the design from Lee et al [20] achieves the highest data rate (10.97 Gbps at 10 iterations), it suffers from a larger chip core area, compared to our proposed design.…”
Section: Throughput Area Efficiency Code Length Area =´mentioning
confidence: 66%
See 1 more Smart Citation
“…The corresponding area efficiency of the proposed work is 76.81 Mbps/mm 2 , whereas the area efficiency obtained by Li et al [11], Park et al [18], Kumawat et al [19], and Lee et al [20] Table 2, it can be concluded that the proposed work is the most area-efficient among the reported LDPC decoders. Although the design from Lee et al [20] achieves the highest data rate (10.97 Gbps at 10 iterations), it suffers from a larger chip core area, compared to our proposed design.…”
Section: Throughput Area Efficiency Code Length Area =´mentioning
confidence: 66%
“…The submatrix size, z, is set to 42 for IEEE 802.11ad, to 81 for IEEE 802.11n, and to 21 for IEEE 802.15.3c applications. First of all, analysis results show that the proposed halfrow pipelined layered LDPC decoder reduces the complexity of nearly all components by half, compared to the fully parallel pipelined layer LDPC decoder design of Kumawat et al [19]. Moreover, the proposed decoder reduces the major area-consuming components, like adders, sign magnitude conversion (SMC), and min comparators, compared to flooding decoders [18,20].…”
Section: Analysis and Comparison Resultsmentioning
confidence: 93%
“…Accordingly, the specific implementation characteristics of NPUs having the proposed dual-tree architecture depend on the characteristics of these subnodes. In order to facilitate a comparison and discussion in this section, we consider NPUs having subnodes which calculate the min (x, y) of two 4-bit unsigned inputs x and y, as used within fixed-point CNPUs performing the MSA 1 [14]. Since this function is non-invertible, the single binary tree structure mentioned in Section I is not viable.…”
Section: Implementation Resultsmentioning
confidence: 99%
“…Alternatively, parallel flexible NPUs may be implemented having the maximum number of inputs and outputs, namely I = D C for CNPUs or I = D V + 1 for VNPUs, where D C and D V refer to the maximum values of d c and d v within the set of supported PCMs, respectively. When used for processing nodes having lower degrees, the unused inputs may be effectively disabled by supplying them with a "null" value [12]- [14]. For the example of VNPUs processing messages in the form of binary fixed-point Logarithmic-Likelihood Ratios (LLRs), each subnode performs the addition of two LLRs.…”
Section: Flexible Npu Architecturesmentioning
confidence: 99%
See 1 more Smart Citation